2022
DOI: 10.1186/s12950-022-00321-y
|View full text |Cite
|
Sign up to set email alerts
|

The immunological function of CXCR2 in the liver during sepsis

Abstract: Background The chemokine receptor CXCR2 and its ligands, especially CXCL8, are crucial mediators for the progression of liver inflammation and liver failure in sepsis. Neutrophils have the highest CXCR2 expression in mice and humans, and their activation via CXCL8 facilitates their migration to the inflamed liver for the clearance of the pathogens and, in turn, the inflammation. Main body In sepsis, the inflammatory insult causes extensive neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…Danirixin and Plerixafor are antagonists of CXCR2 and CXCR4 chemokine receptors, respectively. CXCR2 and CXCR4 are G protein-coupled receptors (GPCR) engaging with several downstream signaling pathways that facilitate various tissue-dependent signals, including cell migration, adhesion, proliferation, survival, and differentiation [ 47 , 48 ]. It has been reported that CXCR2 and CXCR4 can induce apoptosis [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Danirixin and Plerixafor are antagonists of CXCR2 and CXCR4 chemokine receptors, respectively. CXCR2 and CXCR4 are G protein-coupled receptors (GPCR) engaging with several downstream signaling pathways that facilitate various tissue-dependent signals, including cell migration, adhesion, proliferation, survival, and differentiation [ 47 , 48 ]. It has been reported that CXCR2 and CXCR4 can induce apoptosis [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXCR2 and CXCR4 are G protein-coupled receptors (GPCR) engaging with several downstream signaling pathways that facilitate various tissue-dependent signals, including cell migration, adhesion, proliferation, survival, and differentiation [ 47 , 48 ]. It has been reported that CXCR2 and CXCR4 can induce apoptosis [ 48 , 49 ]. Apoptosis regulation is important in EV-A71 replication [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In SIRS, elevated proinflammatory cytokines and widespread accumulation of inflammatory cells in vital organs can lead to organ failure, tissue damage and death. Neutrophils, the first line of defense against infection (2, 3), rely on the activation of CXCR2 receptors to effectively migrate to the site of infection (4). However, in sepsis, overproduction of proinflammatory mediators and increased activation of pattern recognition receptors trigger PI3Kγ, leading to phosphorylation of G protein-coupled receptor kinases (GRKs), that can desensitize CXCR2 on neutrophils (4).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils, the first line of defense against infection (2, 3), rely on the activation of CXCR2 receptors to effectively migrate to the site of infection (4). However, in sepsis, overproduction of proinflammatory mediators and increased activation of pattern recognition receptors trigger PI3Kγ, leading to phosphorylation of G protein-coupled receptor kinases (GRKs), that can desensitize CXCR2 on neutrophils (4). Reduced CXCR2 expression together with overexpression of CCR2 impairs neutrophil migration to the site of infection and favors their accumulation in the microvasculature of various organs, leading to multiple organ dysfunction syndrome (2, 3).…”
Section: Introductionmentioning
confidence: 99%